Determining teaching methods for Malaysian nationhood: towards increasing student patriotism - Wan Mohd Nor, Murni; Adnan, Zatul Himmah; Ku Samsu, Ku Hasnita; Ismail, Mohd Mahadee (Fakulti Pendidikan dan Pembangunan Manusia, Universiti Pendidikan Sultan Idris, 2016)
Studies and surveys that have been conducted indicate that feelings of patriotism and love for the nation seem to have declined, particularly among the younger generation. This makes the teaching and appreciation of Malaysian Nationhood even more necessary than before. However, there are many challenges involved in conducting this course, as many students view the subject skeptically. This study is under the Research Incentive Grant for Teaching and Learning (GIPP) granted by the Centre for Academic Development (CADe) of University Putra Malaysia. The main objective of this study is to determine which teaching strategies for Malaysian Nationhood is effective in increasing student patriotism. In doing so, the study was carried out during class hours, towards the end of semester 1 of 2015/2016 at University Putra Malaysia. The data was obtained from student evaluations and responses of the teaching methods the writer employed when the Malaysian Nationhood class was conducted. In this paper, the writer focuses on student evaluations of two particular course contents; namely the topic of the “The Legislative” and “Social Policies.” Then, the writer analyses whether the students have achieved the learning outcome of these topics, as well as whether their feelings of patriotism increased after the topic has been delivered. In conclusion, the findings of this study suggests that overall, many students have achieved the desired learning outcomes, and have increased feelings of patriotism after the topic was delivered. The findings of this study may serve as a guideline for academicians and policy makers on the methods and strategies that may be effectively employed to encourage and instill feelings of patriotism amongst the youth.